2012
DOI: 10.1194/jlr.d023036
|View full text |Cite
|
Sign up to set email alerts
|

The BUME method: a novel automated chloroform-free 96-well total lipid extraction method for blood plasma

Abstract: This article is available online at http://www.jlr.org implicated in several diverse diseases, such as type 2 diabetes, Alzheimer disease, ( 2 ) and cancer ( 3 ). Lipid analysis has been an important area of research for several decades, and due to technological advances, the fi eld has experienced a renaissance in the last decade. In a modern laboratory, a comprehensive lipid characterization can be performed that generates quantitative data of several hundreds of molecular lipids from several different lipid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
209
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 280 publications
(223 citation statements)
references
References 28 publications
2
209
0
3
Order By: Relevance
“…Over the years some modifi cations to the original solvent system composition have been introduced, tested, and evaluated; although these alterations are not always fully described by the authors, which makes comparison of the lipid content and composition of fl uids in similar pathological conditions somewhat diffi cult. A comparison of the Folch method and the Bligh and Dyer method has shown similar recoveries in the extraction of the predominant phospholipid classes ( 15 ), and similar conclusions were reported in other studies comparing the Folch method with alternative extraction solvent systems (16)(17)(18). Other solvent mixtures that include, for example, hexane ( 19,20 ), butanol ( 18,21 ), ethyl acetate ( 21 ), and more recently tert-butyl methyl ether (TBME) ( 17,(22)(23)(24) are also described in the literature.…”
Section: Sds-page Electrophoresismentioning
confidence: 49%
See 2 more Smart Citations
“…Over the years some modifi cations to the original solvent system composition have been introduced, tested, and evaluated; although these alterations are not always fully described by the authors, which makes comparison of the lipid content and composition of fl uids in similar pathological conditions somewhat diffi cult. A comparison of the Folch method and the Bligh and Dyer method has shown similar recoveries in the extraction of the predominant phospholipid classes ( 15 ), and similar conclusions were reported in other studies comparing the Folch method with alternative extraction solvent systems (16)(17)(18). Other solvent mixtures that include, for example, hexane ( 19,20 ), butanol ( 18,21 ), ethyl acetate ( 21 ), and more recently tert-butyl methyl ether (TBME) ( 17,(22)(23)(24) are also described in the literature.…”
Section: Sds-page Electrophoresismentioning
confidence: 49%
“…A comparison of the Folch method and the Bligh and Dyer method has shown similar recoveries in the extraction of the predominant phospholipid classes ( 15 ), and similar conclusions were reported in other studies comparing the Folch method with alternative extraction solvent systems (16)(17)(18). Other solvent mixtures that include, for example, hexane ( 19,20 ), butanol ( 18,21 ), ethyl acetate ( 21 ), and more recently tert-butyl methyl ether (TBME) ( 17,(22)(23)(24) are also described in the literature. TBME, which was reported to give comparable results to the Bligh and Dyer method in the profi le of human plasma ( 16 ), has become particularly popular for sphingolipidomic studies and the extraction of lipids in fl uids ( 21,23 ).…”
Section: Sds-page Electrophoresismentioning
confidence: 49%
See 1 more Smart Citation
“…Using the method described, our laboratory can routinely extract 400 samples per day. While robotics has obvious advantages ( 24,25 ), we have demonstrated that our method, even with manual handling and extraction of samples, is robust and applicable to cohorts of 1,000 or more samples.…”
Section: Discussionmentioning
confidence: 99%
“…The mobile phase was 88% (vol/vol) solution A (A = acetonitrile/ methanol/water 40:45:15 with 0.2% formic acid, 0.1% ammonia, and 5 μM phosphoric acid) and 12% (vol/vol) solution B (B = isopropanol with 0.2% formic acid, 0.1% ammonia, and 5 μM phosphoric acid), at 1.0 mL/min. The optimal method for purifying copepodamides G and H differed from that of A-F: freeze-dried Calanus tissue (62.2 g) was extracted with methanol five times and extracts were separated by liquid-liquid partitioning with heptane/methanol (98:2) vs. methanol/water/aqueous ammonium hydroxide (94:5:1) (29). Copepodamides G and H were localized to the aqueous fraction, which was then subjected to reversed phase SPE (ENVI-18, 10 g; Supelco), eluting with a step gradient of aqueous methanol (30-100%).…”
Section: Extraction and Bioassay-guided Fractionation Of Compounds Frmentioning
confidence: 99%